2017
DOI: 10.1039/c7ra00399d
|View full text |Cite
|
Sign up to set email alerts
|

Specific pH effect for selective colorimetric assay of glutathione using anti-aggregation of label-free gold nanoparticles

Abstract: An operationally simple colorimetric method for measuring glutathione (GSH) concentration was developed using anti-aggregation of gold nanoparticles (AuNPs) in this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…GSH ( l -γ-glutamyl- l -cysteinyl-glycine) is the most abundant intracellular nonprotein thiol. 24 Because GSH has different vital multitasking functions within our body like maintaining immunity, detoxification of peroxides and free radicals (antioxidant property), and regulations of protein function and cell growth; therefore, imbalance of GSH within our body can cause serious health hazards like cellular damage, liver damage, and even cancer. 25 Keeping these in mind, we have herein reported a simple colorimetric assay to detect and quantify the amount of GSH present.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GSH ( l -γ-glutamyl- l -cysteinyl-glycine) is the most abundant intracellular nonprotein thiol. 24 Because GSH has different vital multitasking functions within our body like maintaining immunity, detoxification of peroxides and free radicals (antioxidant property), and regulations of protein function and cell growth; therefore, imbalance of GSH within our body can cause serious health hazards like cellular damage, liver damage, and even cancer. 25 Keeping these in mind, we have herein reported a simple colorimetric assay to detect and quantify the amount of GSH present.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the dual effect of diverse morphology of mesoporous carbon and catalytic features of Au, Au/OMC shows a very good peroxidase-like activity which is further utilized for the detection of glutathione (GSH). GSH ( l -γ-glutamyl- l -cysteinyl-glycine) is the most abundant intracellular nonprotein thiol . Because GSH has different vital multitasking functions within our body like maintaining immunity, detoxification of peroxides and free radicals (antioxidant property), and regulations of protein function and cell growth; therefore, imbalance of GSH within our body can cause serious health hazards like cellular damage, liver damage, and even cancer .…”
Section: Introductionmentioning
confidence: 99%
“…30 The possibilities of the potential deposition of a sub-monolayer of Ag on the lateral gold nanorods in our case of S3 and S4 specimens were ruled out since the pH of the solution during the synthesis was 6, and thus the possibility of the reduction of Ag + to Ag 0 by ascorbic acid was not possible. 31 Ratiometric absorption-based gold nanosensors 32,33 have been developed by earlier researchers for the sensing and quantication of pH. In our case, it was found that a small change in pH led to the agglomeration of GNs, resulting in a corresponding change in the UV-Vis absorption spectra and color of the specimens under visible light illumination.…”
Section: Resultsmentioning
confidence: 71%
“…Zhong et al, 2010 and Wu et al, 2017 research groups demonstrated the anti-aggregationenabled colorimetric assay of GSH using CI-Au NPs (particle size = 13 nm; conc. = 5/2.5 nM) with sodium piperazinebisdithiocarbamate (ppzdtc; 1.5 µM), cysteine (Cys; 4 µM), and 2-Mercapto-1-methylimidazole (MMI; 2 µM) as aggregation-inducing agents [78][79][80]. Initially, the aggregation-inducing agents functionalized on the surface of NPs reduced the electrostatic repulsion between NPs, which resulted in aggregation with a color change from red to blue.…”
Section: Au Nps-based Colorimetric Quantification Of Bio-analytes Via...mentioning
confidence: 99%